The Impact of Metacognitive Strategy Training on Higher-Order Thinking Skills (HOTS) in High School Mathematics: A Quasi-Experimental Study - Badolo, Mas'ud; Malik, Marwati Abd.; Nur, Rafi'ah; Latifa, Ammang (Three E Science Institute, 2025)
Difficulties developing higher-order thinking skills (HOTS) in mathematics education represent a persistent and significant challenge in educational practice. These skills, such as analysis, evaluation, and creation, are essential for students to succeed in complex problem-solving and adapt to the evolving demands of the 21st century. This study assesses how effectively structured metacognitive training improves high school students' mathematical HOTS. The research employed a quasi-experimental pretest-posttest design involving 72 students from a senior high school in Indonesia, divided into two groups: an experimental group (n=36) that received metacognitive training over one semester, and a control group (n=36) that did not receive any intervention. The primary outcome measure was HOTS scores, assessed through standardized pre-test and post-test instruments designed to evaluate students' higher-order thinking in mathematics. ANCOVA results revealed a significant effect of the metacognitive intervention on HOTS post-test scores (F=44.36; p<0.001; ηp²=0.391), even after controlling for pre-test performance. The experimental group exhibited substantially greater HOTS improvements than the control group. These results prove that structured metacognitive training is an effective pedagogical strategy for fostering advanced mathematical thinking. The findings hold significant implications for curriculum designers, educators, and policymakers aiming to improve mathematics instruction, particularly within the Indonesian context. Future studies involving larger sample sizes, diverse school settings, and longitudinal follow-up are recommended to validate and extend the impact of this intervention.